Natural kaolinitic clay: a remarkable catalyst for highly regioselective chlorination of arenes with Cl-2 or SO2Cl2 - Jayachandran, B.; Phukan, P.; Daniel, Thomas; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2006)
Natural kaolinitic clay containing transition metals such as Fe and Ti in its lattice has been found to exhibit unusual regioselectivity in the liquid-phase chlorination of arenes with either Cl-2 or SO2Cl2 as the chlorinating agent para-Chlorinated products are predominant for most of the substrates with an exceptional case of ortho-selectivity for the chlorination of aniline.
Keywords: Aniline; chlorination; chlorine; ortho-chloroaniline; sulfuryl chloride

Efficient synthesis of antifungal pyrimidines via palladium catalyzed Suzuki/Sonogashira cross-coupling reaction from Biginelli 3,4-dihydropyrimidin-2(1H)-ones - Gholap, Atul R.; Toti, Kiran S.; Shirazi, Fazal; Deshpande, Mukund V.; Srinivasan, Kumar V. (Tetrahedron, 2008)
An efficient regioselective approach to the synthesis of tetrasubstituted pyrimidines was developed by sequential functionalization of easily available Biginelli 3,4-dihydropyrimidine-2(1H)-ones via dehydrogenation, chlorination followed by palladium catalyzed C-C Suzuki/Sonogashira coupling reaction. All the synthesized compounds were evaluated in vitro for their antifungal activities against Candida albicans, Cryptococcus neoformans, Benjaminiella poitrasii, Yarrowia lipolytica, and Fusarium oxysporum, and antibacterial activities against Gram-negative Escherichia coli and Gram-positive Staphylococcus aureus. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activities; Biginelli compounds; chlorination; Oxidation; Pyrimidines; Suzuki coupling

Cu(OTf)(2)-catalyzed alpha-halogenation of ketones with 1,3-dichloro-5,5 `-dimethylhydantoin and N-bromosuccinimide - Jagdale, Arun R.; Chouthaiwale, Pandurang V.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2009)
Copper(II) triflate catalyses efficiently the alpha-halogentation of aryl or alkyl ketones with 1,3-dichloro-5,5'-dimethyl-hydantoin and N-bromosaccinimde to give the corresponding alpha,alpha-dichloroketones and alpha-bromoketones in high yield with excellent product selectivity.
Keywords: Bromination; Catalyst; chlorination; copper (II); Ketone; Lewis acid

Electrochemical deconstruction of waste polyvinylidene chloride (PVDC) to value-added products in batch and flow - Mishra, Subhadip; Kar, Sourav; Rangappa, Raghavendrakumar; Patil, Prashant; Kadam, Vijay; Chikkali, Samir H.; Samanta, Ramesh C. (Chemistry-A European Journal, 2025)
Chlorinated polymers have made enormous contributions to materials science and are commercially produced on a large scale. These chlorinated polymers could be recycled as chlorine sources to efficiently produce valuable chlorinated compounds owing to their facile release of HCl. Although the thermal stability of PVDC is low compared to PVC, this can be advantageous in terms of easy and fast dehydrochlorination. Herein, we report an efficient electrochemical chlorination using poly(vinylidene chloride) (PVDC) as a chlorine source that works in an undivided cell and applies to a good number of examples. This method works on commodity polymers such as waste PVDC-PVC pharma blister film, PVDC-PO multilayer food packaging, and compression molded sheets of Ixan PVDC (with heat stabilizer) with similar efficiency. Furthermore, this method also provides the dechlorination of PVDC up to 98 %, leading to unsaturated dechlorinated material. Converting PVDC into more stable unsaturated compounds, the release of harmful chlorine-containing gases during incineration can be minimized. Additionally, this method is not only restricted to batch processes but an electroflow process for PVDC dechlorination and electrosynthesis has also been demonstrated.
Keywords: chlorination; Electrochemical recycling; Electroflow-synthesis; Graphitic material; Polyvinylidene chloride